The Influence of Product Design through (Online Customer Review) on Purchase Decisions at Korean Beauty Shop on the Shopee Platform - DS, Yudha Mahrom; Herudiansyah, Gumar; Sary, Maretha Puspita (International Journal of Artificial Intelligence Research, 2024)
The purpose of this research is to analyze Korean Beauty Shop's Shopee evaluations in order to draw conclusions about the impact of product design on consumers' final purchasing decisions. One hundred participants were chosen for this study using a purposive sampling method that does not rely on randomness. Numerous linear regressions are employed in the analysis. Research shows that Korean Beauty Shop's product design (as evaluated by online reviews) has a substantial impact on Shopee shoppers' decisions to buy Korean Beauty Shop products. A determination coefficient value of 65.4% indicates that product design (in the form of online customer evaluations) can influence changes in purchase decisions